Regional experience with forage Arachis in other tropical areas: Asia, Africa, and the Pacific - Stür, Werner W.; Ndikumana, J. (International Center for Tropical Agriculture, 1994)
Widespread interest by researchers in the forage potential of Arachis species in Asia, Africa, and the Pacific is relatively recent. But there are a few instances where forage Arachis is being used by farmers for heavily grazed pastures or as a cover crop in fruit tree operations. Forage Arachis species, particularly A. pintoi, are currently under evaluation in many countries and appear to be well adapted to a wide range of climatic and soil conditions in the humid and subhumid tropics. They persist and combine well in mixtures with a large range of grasses, even under heavy grazing. Other advantages are easy vegetative establishment, good spread, good shade tolerance, and the choice of seeding or nonseeding accessions. Limitations to adaptation of the currently available forage Arachis germplasm in Asia, Africa, and the Pacific are low rainfall (<1000 mm average annual rainfall), low-fertility acid soils (pH <5), and low-fertility, high-pH soils (pH >8) such as coralline soils in the Pacific. The use of forage Arachis is being promoted for pasture improvement, particularly in livestock-tree cropping systems, and for heavily grazed pastures. Its potential use as a cover crop for nitrogen fixation, weed control, and erosion control has not been fully investigated.